2011
DOI: 10.1007/s11250-011-9933-y
|View full text |Cite
|
Sign up to set email alerts
|

Uses and flock management practices of scavenging chickens in Wolaita Zone of southern Ethiopia

Abstract: Rearing of scavenging chickens is among the most commonly practiced farm activities in Ethiopia. This system is dominated by indigenous chickens. Output from indigenous chickens is low due to poor management and absence of intense selection that is intended to improve economically important traits. This showed that village chickens are rather evolved for adaptation traits. However, the level of risk is low, and this has made rearing of scavenging chickens a choice of farm activity for smallholder farmers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…It was also observed that none of the respondents vaccinated their birds against any disease in four kebeles under study area (Table 8). This observation was in agreement with Leta and Bekana [25]; Khandait et al [16]; Moges et al [26]; Mengesha et al [27] and Takele and Oli [42] as they all have reported that none of the backyard poultry owner practiced vaccination of birds against poultry diseases in different areas of their study. However, Vaccination has been practiced in Lume and Ada'a districts and this was due to the tremendous and coordinated efforts of livestock experts, development agents (DAs) and field veterinarians in both districts Desalew et al [17].…”
Section: Poultry Healthy Management and Source Of Chickensupporting
confidence: 91%
“…It was also observed that none of the respondents vaccinated their birds against any disease in four kebeles under study area (Table 8). This observation was in agreement with Leta and Bekana [25]; Khandait et al [16]; Moges et al [26]; Mengesha et al [27] and Takele and Oli [42] as they all have reported that none of the backyard poultry owner practiced vaccination of birds against poultry diseases in different areas of their study. However, Vaccination has been practiced in Lume and Ada'a districts and this was due to the tremendous and coordinated efforts of livestock experts, development agents (DAs) and field veterinarians in both districts Desalew et al [17].…”
Section: Poultry Healthy Management and Source Of Chickensupporting
confidence: 91%
“…Nevertheless, the role of poultry as a source of income or as a social tool was reflected in the fact that 54.7% of households had sold and 28.0% had given away poultry during the previous three months. These results are within the range of those from other surveys where sale for income was practiced by 28 to 62% of households (Guèye 1998, Guèye 2000, Dessie and Ogle 2001, Ekue et al 2002, Halima et al 2007, Desta et al 2012. The majority of live poultry sales occurred directly from home through middlemen, but also at markets.…”
Section: Source Exit and Tradesupporting
confidence: 79%
“…Indigenous domestic chickens are often reared under the traditional scavenging system by small-holder farmers in developing countries (Magothe et al, 2012; Desta et al, 2013). The indigenous chickens are popular in these regions because of their tolerance to common poultry diseases and fluctuations in both feed quality and quantity, hence requiring minimum or no input (Desta and Wakeyo, 2012). Because of the natural and artificial selection, indigenous chicken exhibit a wide spectrum of phenotypic and morphologic properties (Wragg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%